Antimicrobial and Cytotoxicity Potential of Acetamido, Amino and Nitrochalcones - Tristão, T. C.; Campos-Buzzi, F.; Corrêa, R.; Cruz, R.C B.; Cechinel Filho, V.; Bella Cruz, A. (Arzneimittelforschung, 2012)
Chalcones constitute one of the major classes of natural products belonging to the flavonoid family, and they have been reported as having a range of important therapeutic activities, including some chalcones are effective as antimicrobial agents. Currently, the search for new structures with antimicrobial activity has been intensified due to the emergence of many strains resistant to antibiotics currently used to treat infectious diseases.3 chalcone series (amino, acetamido and nitrochalcones) were prepared (23 compounds) and evaluated for their antimicrobial and cytotoxic potential. The effects of substituents on their respective activities also was evaluated.The results showed that 4 aminochalcones (2, 4, 8, 9), 3 acetoamidochalcones (10, 14, 18) and 3 nitrochalcones (20, 22, 23), exhibited antifungal effects. The aminochalcones were more toxic than the acetamidochalcones, while the nitrochalcones did not present any toxic effect. It was verified that there seems to be structure-activity correlation in some electron-donating and withdrawing substituents groups in rings A and B of the synthetized chalcone analogues and its antifungal and cytotoxic activity.
Keywords: antibacterial; antifungal; Artemia salina; QSAR; chalcone